Oral glutamine in the prevention of fluorouracil induced intestinal toxicity: a double blind, placebo controlled, randomised trial. Issue 1 (1st January 2001) - Daniele, B; Perrone, F; Gallo, C; Pignata, S; De Martino, S; De Vivo, R; Barletta, E; Tambaro, R; Abbiati, R; D'Agostino, L
Abstract : BACKGROUND: 5-Fluorouracil (FU) in association with folinic acid (FA) is the most frequently used chemotherapeutic agent in colorectal cancer but it often causes diarrhoea. Animal and human studies suggest that glutamine stimulates intestinal mucosal growth. AIM: To determine if oral glutamine prevents changes in intestinal absorption (IA) and permeability (IP) induced by FU/FA. METHODS: Seventy chemotherapy naive patients with colorectal cancer were randomly assigned to oral glutamine (18 g/day) or placebo before the first cycle of FU (450 mg/m 2 ) and FA (100 mg/m 2 ) administered intravenously for five days. Treatment was continued for 15 days, starting five days before the beginning of chemotherapy. IA (d -xylose urinary excretion) and IP (cellobiose-mannitol test) were assessed at baseline and four and five days after the end of the first cycle of chemotherapy, respectively. Patients kept a daily record of diarrhoea, scored using the classification system of the National Cancer Institute (Bethesda, Maryland, USA). Duration of diarrhoea was recorded and the area under the curve (AUC) was calculated for each patient. RESULTS: Baseline patient characteristics and basal values of IP and IA tests were similar in the two arms. After one cycle of chemotherapy, the reduction in IA (d -xylose absorption) was more marked in the placebo arm (7.1% v 3.8%; p=0.02); reduction of IP to mannitol was higher in the placebo arm (9.2% v 4.5%; p=0.02); and urinary recovery of cellobiose was not different between the study arms (p=0.60). Accordingly, the cellobiose-mannitol ratio increased more in the placebo arm (0.037 v 0.012; p=0.04). Average AUC of diarrhoea (1.9 v 4.5; p=0.09) and average number of loperamide tablets taken (0.4 v 2.6; p=0.002) were reduced in the glutamine arm. CONCLUSIONS: Glutamine reduces changes in IA and IP induced by FU and may have a protective effect on FU induced diarrhoea.